I don’t know I just need points lol
Answer:
a reflection across y-axis then translation of 1 unit right and 2 units up.
a clockwise rotation of 180° about the origin then a translation of 1 unit right and 3 units up
a reflection across y-axis then translation of 1 unit right and 1 unit down
a reflection across y = x then a positive rotation of 270° about the origin
Step-by-step explanation:
Answer:
<h2><u>
=</u>
<u>
57
/ 514 </u>
<u>
(Decimal: 0.110895)</u></h2>
Step-by-step explanation:
57
/ 514
<u>= 57
/ 514
</u>
<u>(Decimal: 0.110895)</u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<h2><u>
And if that is not what you are looking for here: </u></h2><h2><u>
</u></h2>
Rewrite the equation as
x
/14
= 5/
7
. x/
14
= 5/
7
Multiply both sides of the equation by
14.14 ⋅ x
/14
= 14
⋅
5
/7
Simplify both sides of the equation.
Tap for fewer steps...
Cancel the common factor of 14
.
Cancel the common factor.
14
⋅ x
/14
= 14
⋅
5
/7
Rewrite the expression.
x
=
14
⋅
5
/7
Simplify 14
⋅ 5/
7
.
Cancel the common factor of 7
.
Factor 7 out of 14
.
x
=
7
(
2
)
⋅
5/
7
Cancel the common factor.
x
=
7
⋅ 2
⋅ 5/
7
Rewrite the expression.
x =
2
⋅
5
Multiply 2 by 5
.
<u>x
=
10</u>
1/3 ln(<em>x</em>) + ln(2) - ln(3) = 3
Recall that , so
ln(<em>x</em> ¹ʹ³) + ln(2) - ln(3) = 3
Condense the left side by using sum and difference properties of logarithms:
Then
ln(2/3 <em>x</em> ¹ʹ³) = 3
Take the exponential of both sides; that is, write both sides as powers of the constant <em>e</em>. (I'm using exp(<em>x</em>) = <em>e</em> ˣ so I can write it all in one line.)
exp(ln(2/3 <em>x</em> ¹ʹ³)) = exp(3)
Now exp(ln(<em>x</em>)) = <em>x </em>for all <em>x</em>, so this simplifies to
2/3 <em>x</em> ¹ʹ³ = exp(3)
Now solve for <em>x</em>. Multiply both sides by 3/2 :
3/2 × 2/3 <em>x</em> ¹ʹ³ = 3/2 exp(3)
<em>x</em> ¹ʹ³ = 3/2 exp(3)
Raise both sides to the power of 3:
(<em>x</em> ¹ʹ³)³ = (3/2 exp(3))³
<em>x</em> = 3³/2³ exp(3×3)
<em>x</em> = 27/8 exp(9)
which is the same as
<em>x</em> = 27/8 <em>e</em> ⁹
Answer:
Step-by-step explanation:
Here we are given that the value of sinA is √3-1/2√2 , and we need to prove that the value of cos2A is √3/2 .
<u>Given</u><u> </u><u>:</u><u>-</u>
•
<u>To</u><u> </u><u>Prove</u><u> </u><u>:</u><u>-</u><u> </u>
•
<u>Proof </u><u>:</u><u>-</u><u> </u>
We know that ,
Therefore , here substituting the value of sinA , we have ,
Simplify the whole square ,
Add the numbers in numerator ,
Multiply it by 2 ,
Take out 2 common from the numerator ,
Simplify ,
Subtract the numbers ,
Simplify,
Hence Proved !